Application of the Discontinuous Galerkin Time Domain Method to the Optics of Bi-Chiral Plasmonic Crystals - Grynko, Yevgen; Förstner, Jens; Meier, Torsten; Radke, André; Gissibl, Timo; Braun, Paul V.; Giessen, Harald
A simulation environment for metallic nanostructures based on the Discontinuous Galerkin Time Domain method is presented. It is used to model optical transmission by silver bi‐chiral plasmonic crystals. The results of simulations qualitatively and quantitavely agree with experimental measurements of transmitted circular polarization.
Keywords: tet_topic_meta

Ultrafast spin-induced polarization oscillations with tunable lifetime in vertical-cavity surface-emitting lasers - Gerhardt, N. C.; Li, M. Y.; Jähme, H.; Höpfner, H.; Ackemann, T.; Hofmann, M. R. (Applied Physics Letters)
We report spin-induced polarization oscillations in vertical-cavity surface-emitting lasers above threshold and at room temperature. The oscillation frequency is 11.6 GHz, which is significantly higher than the modulation bandwidth of less than 4 GHz in the device. The oscillation frequency is determined by an additional resonance frequency in birefringence containing microcavities, which is potentially much higher than the conventional relaxation oscillation frequency. The damping of the oscillations can be controlled by the current, allowing for oscillation lifetimes much longer than the spin lifetime in the device as well as for short bursts potentially interesting for information transmission.

Utilizing an Analytical Approximation for c44E to Enhance the Inverse Method for Material Parameter Identification of Piezoceramics - Rautenberg, Jens; Rupitsch, Stefan J.; Henning, Bernd; Lerch, Reinhard (7th International Workshop on Direct and Inverse Problems in Piezoelectricity)
There has been a lot of progress in finding measurable quantities of high in- formation content for the inverse determination of piezoelectric material properties. Since some material parameters (mainly \textgreek{e}S 11, e15and cE 44) do not or only marginally influence the electrical impedance over frequency, it is not sufficient to look only at the electri- cal impedance of discoidal piezoceramics [1]. Moreover, the parameter sensitivities vary with respect to the diameter-thickness ratio of the disc and the design of an ultrasonic transducer's piezoceramic has to match other requirements than those of a good material characterization [2, 3]. That is why it is still desirable to find model based approaches for parameter identification that either keep the technical effort low (e.g., only an impedance measurement) or increase speed of the inversion procedure. In this contribution we answer the question if an additional analytical approximation of cE 44, strictly following the ideas of Theocaris [4], in conjunction with a single measured elec- trical impedance will be sufficient for an accurate simulation of both, electrical impedance and surface normal velocity of a piezoceramic disc. Thereby, the remaining parameters are identified by means of the Inverse Method. Furthermore, we use the parameter ap- proximation as an initial guess and limiting boundary to speed up the inverse algorithm if both, electrical impedance and surface normal velocity are taken into account within the optimization procedure.

Birefringence and spin controlled ultrafast polarization oscillations in vertical-cavity surface-emitting lasers - Li, Mingyuan; Jähme, Hendrik; Soldat, Henning; Gerhardt, Nils Christopher; Hofmann, Martin; Ackemann, Thorsten (2011 Conference on Lasers and Electro-Optics Europe and 12th European Quantum Electronics Conference (CLEO Europe/EQEC 2011))

Direct limits of infinite-dimensional Lie groups - Glöckner, Helge (Developments and trends in infinite-dimensional Lie theory)
Keywords: 22E65; 22E15; 46A13; 46T05; 54D50

Direct limit constructions in infinite dimensional Lie theory - Dahmen, Rafael

Phosphonium Salt Catalyzed Addition of Diethylzinc to Aldehydes - Werner, Thomas; Riahi, Abdol; Schramm, Heiko (Synthesis)
Keywords: T2

Interaction of phase‐transformations and plasticity – a multi‐phase micro‐sphere approach - Ostwald, Richard; Bartel, Thorsten; Menzel, Andreas (PAMM)
Abstract We present an efficient model for the simulation of solid to solid phase‐transformations in polycrystalline materials. As a basis, we implement a scalar‐valued Gibbs‐energy‐barrier‐based phase‐transformation model making use of statistical physics. In this work, we particularly adopt the model for the simulation of phase‐transformations between an austenitic parent phase and a martensitic tension and compression phase. The incorporation of plasticity phenomena is established by enhancing the Helmholtz free energy functions of the material phases considered, where the plastic driving forces acting in each phase are derived from the overall free energy potential. The coupled model is embedded into a micro‐sphere formulation in order to simulate three‐dimensional boundary value problems—a technique well‐established in the context of computational inelasticity at small strains. It is shown that the model is capable of reflecting experimentally observed behaviour. (© 2011 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)

Experimental and Computational Investigation of Machining Processes for Functionally Graded Materials - Biermann, D.; Menzel, A.; Bartel, T.; Höhne, F.; Holtermann, R.; Ostwald, Richard; Sieben, B.; Tiffe, M.; Zabel, A. (Procedia Engineering)

Preserving Charge and Oxidation State of Au(III) Ions in an Agent-Functionalized Nanocrystal Model System - Müllegger, Stefan; Schöfberger, Wolfgang; Rashidi, Mohammad; Lengauer, Thomas; Klappenberger, Florian; Diller, Katharina; Kara, Kamuran; Barth, Johannes V.; Rauls, Eva; Schmidt, Wolf Gero; Koch, Reinhold (ACS Nano)

Electrically Detected Electron-Spin-Echo Envelope Modulation: A Highly Sensitive Technique for Resolving Complex Interface Structures - Hoehne, Felix; Lu, Jinming; Stegner, Andre R.; Stutzmann, Martin; Brandt, Martin S.; Rohrmüller, Martin; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Letters)

Band offsets in cubic GaN/AlN superlattices - Mietze, C.; Landmann, M.; Rauls, E.; Machhadani, H.; Sakr, S.; Tchernycheva, M.; Julien, F. H.; Schmidt, Wolf Gero; Lischka, K.; As, Donat Josef (Physical Review B)

Asymmetric saddling of single porphyrin molecules on Au(111) - Müllegger, S.; Rashidi, M.; Lengauer, T.; Rauls, E.; Schmidt, Wolf Gero; Knör, G.; Schöfberger, W.; Koch, R. (Physical Review B)

Microscopic structure and energy transfer of vacancy-related defect pairs with Erbium in wide-gap semiconductors - Konopka, A.; Greulich-Weber, S.; Dierolf, V.; Jiang, H.X.; Gerstmann, Uwe; Rauls, E.; Sanna, S.; Schmidt, Wolf Gero (Optical Materials)

Methane adsorption on graphene from first principles including dispersion interaction - Thierfelder, C.; Witte, M.; Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (Surface Science)

Driving forces for the adsorption of cyclopentene on InP(001) - Favero, P.P.; Ferraz, A.C.; Schmidt, Wolf Gero; Miotto, R. (Surface Science)

Influence of Na adsorption on the quantum conductance and metal-insulator transition of the In-Si(111)(4×1)–(8×2) nanowire array - Schmidt, Wolf Gero; Babilon, M.; Thierfelder, C.; Sanna, S.; Wippermann, S. (Physical Review B)

Imaging of the Ferroelectric Domain Structures by Confocal Raman Spectroscopy - Berth, Gerhard; Hahn, Wjatscheslaw; Wiedemeier, Volker; Zrenner, Artur; Sanna, Simone; Schmidt, Wolf Gero (Ferroelectrics)

Group-VII point defects in ZnSe - dos Santos, L. S.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

Tight‐binding model for the electronic and optical properties of nitride‐based quantum dots - Schulz, S.; Mourad, D.; Schumacher, Stefan; Czycholl, G. (physica status solidi (b))
Abstract Two slightly different, efficient tight‐binding (TB) models for the description of the electronic properties of nitride‐based semiconductor quantum dots (QDs) have been developed and applied to the calculation of the electronic one‐particle spectrum of these structures. Using these one‐particle QD‐states, dipole and Coulomb matrix elements can be calculated, from which the optical properties of these systems can be obtained. These TB calculations have been performed for nitride‐based QDs with a cubic zincblende structure and those with a wurtzite crystal structure. In this paper, we discuss the general methodology used and the results obtained for the electronic one‐particle states and energies, for the dipole and Coulomb matrix elements, and for the excitonic optical emission and absorption spectra.